Is the Macronutrient Intake of Formula-Fed Infants Greater Than Breast-Fed Infants in Early Infancy? - Shelly N. Hester; Deborah S. Hustead; Amy D. Mackey; Atul Singhal; Barbara J. Marriage (Journal of Nutrition and Metabolism)
Faster weight gain early in infancy may contribute to a greater risk of later obesity in formula-fed compared to breast-fed infants. One potential explanation for the difference in weight gain is higher macronutrient intake in formula-fed infants during the first weeks of life. A systematic review was conducted using Medline to assess the macronutrient and energy content plus volume of intake in breast-fed and formula-fed infants in early infancy. All studies from healthy, term, singleton infants reporting values for the composition of breast milk during the first month of life were included. The energy content of colostrum (mean, SEM: 53.6±2.5 kcal/100 mL), transitional milk (57.7±4.2 kcal/100 mL), and mature milk (65.2±1.1 kcal/100 mL) was lower than conventional infant formula (67 kcal/100 mL) on all days analyzed. The protein concentration of colostrum (2.5±0.2 g/100 mL) and transitional milk (1.7±0.1 g/100 mL) was higher than formula (1.4 g/100 mL), while the protein content of mature milk (1.3±0.1 g/100 mL) was slightly lower. Formula-fed infants consume a higher volume and more energy dense milk in early life leading to faster growth which could potentially program a greater risk of long-term obesity.